Revealing the Social Values through Signs in the Novel Paper Towns by John Green - Mutmainah Ashari; Rosmiati Rosmiati; Ulum Janah (Faculty of Letters Universitas Balikpapan, 2019)
This research analyzes about the signs represented social values in the novel Paper Towns.There are two objectives that become the purpose of this study: 1) to explain the types ofsocial values in the novel Paper Towns by John Green and 2) to analyze the signs whichreveal the social values in the novel Paper Towns by John Green. The theory used in thisresearch is the Semiotics approach by using theory of Charles Sanders Peirce, there areQualisign, Sinsign and Legisign. The methodology used in this study is descriptivequalitative research to explain the data, because the data are analyzed in the form of wordsand sentences. The data are taken from the sentences and the conversation in the text in thenovel Paper Towns by John Green. The result of the research, the researcher found 4 typesof social values. There are stimulation, hedonism, security, and conformity. The researcherfound signs of words in the novel and analyze the signs using Charles Sanders Peirce'stheory and then the researcher revealed social values through signs based on the types ofsocial values by Schawartz.